(untitled) (Journal of Engineering, 2010)
The effects of incoming wakes of upstream rotor on the flow field in a low pressure turbine cascade are investigated. The flow field is studied numerically with and without inlet wake. The rotor effect is represented by moving bars that produce passing wakes at the entrance of the stator. The flow field is analyzed numerically by solving the steady and unsteady forms of the two-dimensional compressible Reynolds-averaged Navier-Stokes equations. Steady flow is performed without wake while the unsteady flow is performed with periodic inlet wake for Reynolds number of order 105. A k- turbulence model is used to obtain the eddy viscosity. The Cartesian velocity components and pressure on a collocated (non-staggered) grid are used as dependent variables in the momentum equations, which discretized by finite volume method, body fitted coordinates are used to represent the complex blade geometry accurately, and grid generation technique based on elliptic partial differential equations is employed. SIMPLE algorithm is used to adjust the velocity field to satisfy the conservation of mass. The results show that the wake passing produces unsteady pressure field in the direction of the rotor traverse. The comparison with the experimental data is acceptable and there is similar trend between the prediction and experimental data, except at the separation flow region due to the limitation of the turbulence model.